Personality has minor effects on panel attrition - David Richter; John Körtner; Denise Saßenroth (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In light of the recent interest in using longitudinal panel data to study personality development, it is important to know if personality traits are related to panel attrition. We analyse the effects of personality on panel drop-out separately for an 'older' subsample (started in 1984), a relatively 'young' subsample (started in 2000), and a 'new' subsample (started in 2009) of the German Socio-Economic Panel (SOEP) study. We found that openness slightly decreases the probability of panel drop-out in all three samples. For the 'older' subsample only, we found a small negative effect of agreeableness on panel drop-out. We control for age, sex, education, migration background, and the number of inhabitants in the region of the respondents.
Keywords: 330